Factibilidad para sustitución de sistemas de refrigeración que utilizan r-22 por sistemas que funcionan con nh3 en el área de fabricación de galletas con crema - Bermeo Rodríguez., Hugo E. (2009)
This thesis describes a study for a professional job, has a company that produces food for mass consumption. The project involves designing and implementing a new cooling system with the particularity that employs an ecological refrigerant for air conditioning of an area, the same parameters that require specific temperature and relative humidity for the production of the biscuits with cream. The reference design will include the system thermal load calculation, equipment selection, pipe network design, system design of pipelines for transport of cold air, details and specifications for construction and installation schedule Cooling System In this work always be considering the fact that an efficient design results in an operating system that has an economic and environmentally friendly for that reason the end of this paper presents a cost analysis of the entire project and compared with the system as currently installed electric power consumption is concerned.